Design of host computer system for induction heating power supply based on LabVIEW - Jie, Liu; Jianwei, Mei; Xiangcheng, Zhou (2020 IEEE 2nd International Conference on Civil Aviation Safety and Information Technology (ICCASIT, 2020)
In view of the actual use of induction heating power supply, there are some problems such as the upper computer system is not perfect. Based on the idea of virtual instrument, a host computer system of induction heating power supply based on LabVIEW is designed in this paper. The system improves the shortcomings of traditional measurement and control instruments, and improves the degree of automation of the system. The main tasks of this paper include: the development of serial communication, the establishment of database access, the progress of each functional module of upper computer.